Distribusi butiran sedimen di pantai Dalegan, Gresik, Jawa Timur - Ahmad Bayhaqi; Caesar M.A. Dungga (Depik, 2015)
Abstract. Erosion or sedimentation process is an important thing to know the condition of beach. That process can be noticed from sediment’s feature. Meanwhile, the particle size of sediment is of paramount thing than other feature such as speed of deposition and mass density. This study was conducted to find out distribution of particle size in Dalegan beach. Samples were collected from 15 sampling sites in different zones (zone A: lowest tide zone, zone B: 5 meters from zone A, zone C: 5 meters from zone B) with purposive sampling method. Sediments were grouped by Wentworth scale. Sieve and Granulometry analysis were used in this research to know type of sediment and its distribution. Results of study showed that the dominant of sediment type is fine sand. The spreading of this type be more dominant to the open sea and west direction along the coast. The condition of this spreading can be potential to make a change of beach condition.Keywords: Particle size; Sediment; Fine Sand; GranulometryAbstrak. Proses erosi dan sedimentasi adalah hal yang penting untuk mengetahui kondisi pantai. Proses tersebut dapat diketahui dengan sifat-sifat sedimen. Ukuran butir sedimen merupakan hal yang terpenting diantara sifat-sifat sedimen yang lainnya seperti kecepatan endap dan kepadatan massa. Tujuan penelitian ini ialah untuk mengetahui distribusi ukuran butir sedimen di Pantai Dalegan. Sampel dikumpulkan dari 15 titik sampling yang berbeda dari 3 zona (zona A : zona surut terendah, zona B : zona 5 meter dari zona A dan zona C : zona 5 meter dari zona B) menggunakan purposive sampling method.  Sedimen dikelompokkan dengan skala Wenworth. Analisis ayakan dan granulometri digunakan untuk mengetahui jenis sedimen dan penyebaran ukuran butirnya. Hasil penelitian menunjukkan bahwa jenis sedimen yang mendominasi adalah pasir halus. Penyebaran jenis sedimen ini lebih cenderung dominan ke arah laut terbuka dan semakin ke barat dari pantai. Kondisi penyebaran distribusi ukuran butir sedimen dapat berpotesi membuat perubahan pada kondisi pantai.Kata kunci : Ukuran Butir; Sedimen; Pasir Halus; Granulometri